Application of Cupping Therapy in TN "A" for Pain Problems in Gouty Arthritis Clients - Abdurrohim, Abdurrohim; Munir, Zainal; Azizah Heru, Maulidiyah Junnatul (Research of Service Administration Health and Sains Healthys, 2024)
Introduction: Gout arthritis is one of the diseases that often occurs in the elderly, gout is caused by people who consume a lot of food and drinks containing purines such as tea and coffee. High uric acid can cause a number of diseases, including rheumatoid arthritis, gout, muscle strophism, kidney failure and kidney stones, myocardial infarction, diabetes, and premature death. Cupping therapy or known as bekam is a treatment method by removing damaged blood from the body through the surface of the skin. Cupping functions to reduce swelling of sore joints, cupping removes prostaglandin substances from the sore spot so as to reduce pain, in addition, cupping triggers the secretion of endorphins and enkephalins in the body which function as natural pain relievers. Research method: The approach method used in this writing is a descriptive writing approach using a case study design. Research results: After being given nursing care and implementing nursing, it was found that cupping therapy had an effect on reducing the intensity of pain in patients with gout arthritis. Conclusion: conclude that the implementation of cupping therapy is very appropriate to reduce the intensity of pain in clients.